Manajemen Layanan Teknologi Informasi pada Domain Service Operation di Perguruan Tinggi yang ada di Indonesia - Albert, Brian; Tantono, Calvin; Chainatra, Derick; Halim, Marcello Stevin; Dickson, Nicholas (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The use of information technology which is increasingly developing in increasing effectiveness, especially at tertiary institutions in Indonesia is very useful. In academics, the use of this technology helps tertiary institutions in dealing with a problem that is in it. But there are several factors to a problem in the use and management of information technology. This can be overcome by implementing an Information Technology Infrastructure Library Version 3 framework. Management is carried out in the service operation domain due to the high constrained focus on that domain. There are differences in each tertiary institution analyzed using this framework. Significant differences in each college with each research method used to create a descriptive. Assessment and recommendations are different techniques for each college in a result of the journal. There is a discovery in determining the answer at each stage of higher education research. The results obtained at each tertiary institution are different for each indicator or process in the service operation.